Impact of Iron, Silicon and Boron Nanoparticles on the AC Breakdown Voltage of Rice Bran Oil in the Presence of CTAB - Mohd Taufiq, Ishak; Nur Sabrina, Suhaimi; Nurul ‘Izzati, Hashim; Ja’afar, Adnan; Fakroul Ridzuan, Hashim (Semarak Ilmu Publishing, 2025)
The power and energy sector is embracing modern technology across various scientific fields to enhance efficiency, particularly with the integration of distributed generation and smart grids. A crucial element in power transmission and distribution is the Transformer, which is commonly filled with oil and used in both high voltage transmission and low voltage distribution. To improve the operational efficiency of these large machines, researchers are conducting studies to develop insulating oils with high dielectric strength. This research aims to enhance the dielectric properties of natural oil-based insulating fluids by incorporating suitable nanoparticles. Edible oil such as rice bran oil has been selected for this purpose. Nanoparticles such as iron (Fe3O4), silicon (SiO2) and Boron (h-BN) have been chosen as additives. The breakdown Voltage is compared among different samples. The impact of cetyltrimethylammonium bromide (CTAB) as a surfactant was also investigated. The results obtained demonstrate the potential to create natural vegetable-based oils with nanomaterial additives, such as white graphene, which possess superior qualities compared to traditional mineralbased transformer oils. The concentration of each nanoparticle used is 0.01, 0.025, and 0.05 g/L. Two-step processes involving sonication and drying are employed to disperse the nanoparticles. The AC breakdown voltage is assessed following the guidelines of the IEC 60156 standard. The findings indicate that the addition of 0.025g/L of iron nanofluid significantly enhances the AC breakdown voltage of rice bran oil, while boron nanofluid demonstrates a moderate effect, with the highest improvement observed at a concentration of 0.01g/L. In contrast, the presence of silicon nanofluid results in the lowest breakdown voltage among the three mentioned nanoparticles. The inclusion of CTAB in RBO nanofluids reduces the AC breakdown voltage. Iron, silicon, and boron show potential for future transformer applications.